2017
DOI: 10.1038/cddis.2017.242
|View full text |Cite
|
Sign up to set email alerts
|

Upconversion nanoparticle-mediated photodynamic therapy induces autophagy and cholesterol efflux of macrophage-derived foam cells via ROS generation

Abstract: Macrophage-derived foam cells are a major component of atherosclerotic plaques and have an important role in the progression of atherosclerotic plaques, thus posing a great threat to human health. Photodynamic therapy (PDT) has emerged as a therapeutic strategy for atherosclerosis. Here, we investigated the effect of PDT mediated by upconversion fluorescent nanoparticles encapsulating chlorin e6 (UCNPs-Ce6) on the cholesterol efflux of THP-1 macrophage-derived foam cells and explored the possible mechanism of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 41 publications
2
52
0
Order By: Relevance
“…The data are shown as the mean ± standard deviation of three experiments. 49 The ROS production detection results show that in 25 µg/mL of curcumin-LDH and then PDT the ROS production is higher than control even than 100 µg/mL. In IC 50 there are not any autophagic vacuoles may be it is due to another cell death mechanism under PDT.…”
Section: Discussionmentioning
confidence: 92%
“…The data are shown as the mean ± standard deviation of three experiments. 49 The ROS production detection results show that in 25 µg/mL of curcumin-LDH and then PDT the ROS production is higher than control even than 100 µg/mL. In IC 50 there are not any autophagic vacuoles may be it is due to another cell death mechanism under PDT.…”
Section: Discussionmentioning
confidence: 92%
“…45 It is generally accepted that ROS are tumour suppressors that are implicated in tumorigenesis, progression and survival phenotypes. 47,48 ROS is a double-edged sword and the influence of ROS within cancer cells, whether they are favourable or harmful, may depend on several factors, such as cell type, stimulus, duration, specificity and levels of ROS. 47,48 ROS is a double-edged sword and the influence of ROS within cancer cells, whether they are favourable or harmful, may depend on several factors, such as cell type, stimulus, duration, specificity and levels of ROS.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that a few studies have shown that AKT was also found to be down-regulated by ROS in cancer cells. 47,48 ROS is a double-edged sword and the influence of ROS within cancer cells, whether they are favourable or harmful, may depend on several factors, such as cell type, stimulus, duration, specificity and levels of ROS.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, all these lipoproteins increase autophagic flux in macrophages, and autophagy depletion in these cells results in diminished cholesterol efflux to apoA-I. The autophagy inhibitor 3-methyladenine and an ATG5 siRNA were found to significantly attenuate autophagy, subsequently suppressing the ABCA1-mediated cholesterol efflux (48). Biochemical studies have demonstrated that the accumulation of cholesterol esters in prostate cancer cells is the result of loss of the tumor suppressor PTEN and activation of the PI3K/Akt pathway.…”
Section: Association Of Abca1 With Apoptosis and Autophagy In Prostatmentioning
confidence: 99%